2014
DOI: 10.1111/cmi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Contact-induced apical asymmetry drives the thigmotropic responses ofCandida albicanshyphae

Abstract: Filamentous hyphae of the human pathogen, Candida albicans, invade mucosal layers and medical silicones. In vitro, hyphal tips reorient thigmotropically on contact with small obstacles. It is not known how surface topography is sensed but hyphae lacking the cortical marker, Rsr1/Bud1, are unresponsive. We show that, on surfaces, the morphology of hyphal tips and the position of internal polarity protein complexes are asymmetrically skewed towards the substratum and biased towards the softer of two surfaces. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 48 publications
4
64
0
Order By: Relevance
“…Single-Cell Manipulation of Growth Rate Impacts the Stability of GTP-Cdc42 Polarity Polar domains of the active form of the Rho-like GTPase Cdc42 promote local growth. Studies in yeast and fungal cells have shown that polar domains can oftentimes become unstable, assembling and disassembling at successive positions around the cell surface [5,7,9,[11][12][13]. Motivated by the observation that faint and unstable domains are associated with slow surface growth [7,9,12], we sought to dissect the causal-effect relationships between growth and polarity, and assay in a systematic manner the impact of modulating surface growth rate on polarity stability.…”
Section: Resultsmentioning
confidence: 99%
“…Single-Cell Manipulation of Growth Rate Impacts the Stability of GTP-Cdc42 Polarity Polar domains of the active form of the Rho-like GTPase Cdc42 promote local growth. Studies in yeast and fungal cells have shown that polar domains can oftentimes become unstable, assembling and disassembling at successive positions around the cell surface [5,7,9,[11][12][13]. Motivated by the observation that faint and unstable domains are associated with slow surface growth [7,9,12], we sought to dissect the causal-effect relationships between growth and polarity, and assay in a systematic manner the impact of modulating surface growth rate on polarity stability.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, the filamentous forms (hyphae and pseudohyphae) were considered pathogenic, whereas yeasts were primarily viewed as commensals. Hyphae are intrinsically invasive on solid media and hyphal tip cells exhibit thigmotropism, or the unusual ability to ‘track’ along substrate surface irregularities 31 (reviewed in 32 ). Moreover, hyphae express numerous cell type-specific virulence factors such as adhesins (for example, Hwp1, Als3, Als10, Fav2 and Pga55), tissue-degrading enzymes (for example, Sap4, Sap5 and Sap6), antioxidant defense proteins (for example, Sod5), and even a recently described cytolytic peptide toxin (Ece1).…”
Section: Classic Cell Typesmentioning
confidence: 99%
“…fumigatus [27], while others have used microfluidic techniques to identify immunosuppressive fungal metabolites [28]. For microbiologists, microfluidics has provided a useful platform for imaging active Candida hyphal growth at high resolution, revealing that internal polarity protein complexes are asymmetrically skewed toward softer substratum [29]. …”
Section: Introductionmentioning
confidence: 99%